Development of Android-Based E-LKPD Assisted by Liveworksheet in Basic Accounting Subjects at SMKN 1 Medan - Sitorus, Putri Rahmadani; Zainal, Andri; Haryadi, Haryadi; Hasibuan, Ali Fikri; Thohiri, Roza (Edumaspul: Jurnal Pendidikan, 2025)
This study aims to develop an android-based e-LKPD assisted by liveworksheet for basic accounting subjects at SMKN 1 Medan using the 4D development model (Define,Design, Develop, Disseminate) and the research & Development (R&D) BSNP standards, assess its practicality thorough responses from accounting teachers and students, and measure the product’s effectiveness tho]rough post-test results. The research process began with a needs analysis conducted through interviews with accounting teachers and distributing questionnaires to students. Subsequently, a draft of the e-LKPD was designed and validated by material and media experts. The validity test results showed that content feasibility scored 92,3%, presentation feasibility 95%, language feasibility 96%, and media feasibility 94%, all categorized as very valid. The practicality test revealed teacher responses regarding interest and language at 91,6%, with language feasibility at 83,3%. Meanwhile, student responses include interest at 82,6% material at 80,5%, and language at 82,9%, all classified as very practical. The effectiveness test through post-test results showed a student pass rate 85,7%, categorized as very good.Based on these findings, the android-based e-LKPD assisted by liveworksheet is declared feasible, practical, and effective for use in basic accounting learning at SMKN 1 Medan.